Náboženský turismus, nebo turismus jako náboženství?: Několik poznámek ke studiu vztahů mezi náboženstvím a turismem = Religious tourism or Tourism as a religion? : Several remarks on the study of relations between religion and tourism - Hron, Jan (Religio, 2017)
The aim of this study is to present the main approaches of research into the connections between religion and tourism. The first part focuses on the concept of religious tourism. This term is used primarily to accommodate the needs of the tourism industry in order to distinguish among various types of religious travel. Religious tourism is either defined as a form of pilgrimage without religious motives and practices or as an all-encompassing category for all types of travel exhibiting religious features including both pilgrimage with and without religious motives and practices. The rest of the paper discusses the role of pilgrimage in the analysis of the relationship between religion and tourism. Pilgrimage is viewed by many scholars as a sacred journey and this view deeply affects the interpretation of tourism and its relation to religion. Tourism is distinguished from the pilgrimage according to several dichotomies (sacred/profane, religious/secular, ascetic/hedonistic). Some of these dichotomies are used to demonstrate tourism as a certain type of new religion. However, these approaches are misleading and based on false assumptions. This article argues that studies inspired by performative, mobile and spatial turns provide a more nuanced, unbiased, complex, and accurate picture.